Abundance : the future is better than you think - Diamandis, Peter H. (Free Press, 2012)
The authors document how four forces--exponential technologies, the DIY innovator, the Technophilanthropist, and the Rising Billion--are conspiring to solve our biggest problems. "Abundance" establishes hard targets for change and lays out a strategic roadmap for governments, industry and entrepreneurs, giving us plenty of reason for optimism.